Beurteilung des Milchquotenbor̈sensystems in Deutschland - Bernhard Brum̈mer; Jens-Peter Loy; Carsten Struve (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2003)
– In this paper the newly established rules for trading milk quotas in Germany are analyzed. These regulations have been in force since April 2000. Following a brief historical review of the quota system, the major changes in economic incentives regarding trading milk and the expected welfare implications are derived. Next, the effects of the new trading rules on quota prices in comparison to a reference system (sealed bid double auction) are discussed. In the empirical part the significance of the theoretical effects is illustrated. Recent changes in the regulations for quota trade are shown to have little effect in terms of mitigating these problems.
Keywords: 330; Milchpolitik; Auktion; Auktionstheorie; Agrarökonomik; Deutschland